A League of His Own - Blood, Peter Ray (Trinidad Guardian)
Liam Teague, currently a sophomore at Northern Illinois University, continues to astound his teachers, classmates and fans through his virtuosity and knowledge of pan. Teague created history by becoming the first pannist to be accompanied by a full symphony orchestra when he performed with the Chicago Sinfonietta. Teague comments on the range of players ability and to need to streamline the structure of steel orchestras.
Keywords: Musicians -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel drum (Musical instrument) -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago